Apex Predators, Rockshelters, and Zoonoses in the Patagonian Holocene - Fugassa, Martín Horacio (2017)
Carnivorous mammals are a trophic guild with an important role in the dissemination of parasite infective stages (larvae, eggs, cysts, and oocysts). In the present study, new samples of coprolites attributed to carnivorous mammals, obtained from 2 archaeological caves, were analyzed for the presence of parasites with the aim to increase the knowledge about parasites in rockshelters that could have spread to humans and other mammals. To this purpose, fragments of 3 coprolites from Cerro Casa de Piedra, cave 5 and cave 7, were examined. Coprolites were rehydrated in aqueous trisodium phosphate and processed by spontaneous sedimentation. High parasite richness was observed and new parasite species for archaeological contexts were found. The parasitological findings in Puma concolor coprolites associated with caves suggest the importance of these carnivores in the dissemination of parasites in areas with high re-use of space and steady conditions of temperature, humidity, and radiation.